Evidence of the occurrence, detection, and ecotoxicity studies of perfluorooctanesulfonic acid (PFOS) and perfluorooctanoic acid (PFOA) in aqueous environments - Omotola, Elizabeth Oyinkansola; Ohoro, Chinemerem Ruth; Amaku, James F; Conradie, Jeanet; Olisah, Chijioke; Akpomie, Kovo G; Malloum, Alhadji; Akpotu, Samson O; Adegoke, Kayode Adesina; Okeke, Emmanuel Sunday (Journal of environmental health science & engineering, 2025)
Perflorochemicals (PFCs), among which are the most commonly detected perfluorooctanesulfonic acid (PFOS) and perfluorooctanoic acid (PFOA), are persistent emergent contaminants of concern in recent times. These compounds have been reported for their cytotoxicity, genotoxicity, carcinogenicity, immunotoxicity, and developmental toxicities. Meanwhile, they have been detected in diverse matrices such as soil, sediment, and, surprisingly, in serum and even breastmilk. Worrisomely, these compounds are detected in drinking water across the globe, aquaculture water, and other surface waters. Thus, it was important to appraise the studies conducted on PFOS and PFOA to provide an overview of the environmental status of contamination regarding them. The present review article sought to provide insights into the occurrence patterns and ecotoxic effects of both pollutants in the water ecosystems within five continents of the world. Based on the information gathered in this article, the ∑ P F O S concentration (ng/L) within the five continents is in the order Europe > Asia > Africa > North America > South America, while the ∑ P F O A level (ng/L) is in the order Europe > Asia > South America > Africa > North America. The study also investigated the previous works that have been conducted regarding the diverse elimination technologies employed for the removal of these pollutants from the aqueous environments, with plasma combined with surfactant process being the most efficient. Generally, studies on PFOS/PFOA are still scanty when compared to those on pharmaceuticals and personal care products (PPCPs), especially in North America. The information gathered in this study could be useful in establishing thresholds of PFOA and PFOS environmental levels and be adopted by appropriate authorities as safety guidelines.
Keywords: Perfluorooctanesulfonic acid; Perfluorochemicals; Contamination; Perfluorooctanoic acid; Ecotoxicity